Production Systems And Income Generation From The Smallholder Beef Cattle Farming In Yogyakarta Province, Indonesia - Widiati, Rini; Widi, Tri Satya Mastuti (ANIMAL PRODUCTION, 2016)
This study was aimed to determine the production systems of beef cattle which can generate the income of smallholder farmers. The study was conducted in Bantul and Sleman Regencies, Yogyakarta Province, Indonesia. In total of 210 beef cattle farmers were involved in semi structural interview. Data was collected in the dry season (July to September) of 2015.Â  Descriptive analysis was carried out for the demographic, social, economic characteristic of respondents and beef cattle farm practices. Enterprise budgeting of beef cattle farms was made to analyse farm profit, return to management and family labour that could be used in further planning for better business management. Beef cattle farming founded as an alternative that can be developed in rural communities. In order to generate the incomes in both systems, breeding and fattening, production system in term of feeding practices has to be improved so that the cost can be reduced. Scientific processing of manure has to be done for value addition in the farming system. Calving interval has to be improved in breeding system, that the best condition is 12 months and the existing condition on the respondents was 16 months. For fattening, optimizing the duration for fattening period less than 3.6 months is the best improvement. Government policy is needed to improve beef farm economic condition especially in breeding farm.